Rebranding Kampoeng Lama Tourism Village Through Community Empowerment to Achieve Sustainable Tourism: Rebranding Desa Wisata Kampoeng Lama Melalui Pemberdayaan Masyarakat Untuk Mewujudkan Pariwisata Berkelanjutan - Ramadhan, Ikhlas; Nasution, Dayan Hakam Baihaqi; Tanjung, Alra Dayndivie; Lubis, Muhammad Rizki; Risandy, Muhammad Eman (Institut Pariwisata dan Bisnis Internasional, 2024)
Kampoeng Lama Village in Pantai Labu District, Deli Serdang Regency, has faced a decline in its image and tourism sustainability following a fire incident at the Paloh Naga Agrotourism site. This incident has negatively impacted the village's attractiveness and overall tourism potential. This study investigates the rebranding of Kampoeng Lama as a sustainable tourism destination through community empowerment. Employing a qualitative descriptive method with a field study approach, data were collected through interviews with key stakeholders, including the heads of the village-owned enterprise (BUMDes) and the tourism community empowerment group (Pokdarwis), along with observations and documentation. The findings reveal critical challenges, such as insufficient promotion, a weakened agrotourism image, and inadequate tourism facilities. To address these issues, a rebranding strategy centered on community empowerment is proposed. Key initiatives include engaging the younger generation in programs like the